Ernest Bevin - BBC radio broadcast, June 1943 (pg. 2) (London, 1941)
1941 1939-1945 "Ernest Bevin - BBC radio broadcast, June 1943 (pg. 2)" [HFR0102b], 1941 Ernest Bevin, Minister for Labour and National Service, gave regular broadcasts on the British Broadcasting Corporation Home and Overseas Services between 1940 and 1945. This broadcast was made on 1 June 1943 at Brentford, West London, to mark the 2nd anniversary of Workers Playtime, a comedy and music radio programme, initiated to raise the morale of war workers. The variety show, which ran 1941 - 1964, toured the country with the Ministry of Labour choosing which factory canteens the show would visit. Each programme ended by wishing "Good Luck All Workers!".